Nuclear protein phosphatase 2A dephosphorylates protein kinase A-phosphorylated CREB and regulates CREB transcriptional stimulation. - Wadzinski, B E (1993)
Cyclic AMP (cAMP)-dependent protein kinase A (PKA) stimulates the transcription of many eucaryotic genes by catalyzing the phosphorylation of the cAMP-regulatory element binding protein (CREB). Conversely, the attenuation or inhibition of cAMP-stimulated gene transcription would require the dephosphorylation of CREB by a nuclear protein phosphatase. In HepG2 cells treated with the protein serine/threonine (Ser/Thr) phosphatase inhibitor okadaic acid, dibutyryl-cAMP-stimulated transcription from the phosphoenolpyruvate carboxykinase (PEPCK) promoter was enhanced over the level of PEPCK gene transcription observed in cells treated with dibutyryl-cAMP alone. This process was mediated, at least in part, by a region of the PEPCK promoter that binds CREB. Likewise, okadaic acid prevents the dephosphorylation of PKA-phosphorylated CREB in rat liver nuclear extracts and enhances the ability of PKA to stimulate transcription from the PEPCK promoter in cell-free reactions. The ability of okadaic acid to enhance PKA-stimulated transcription in vitro was entirely dependent on the presence of CREB in the reactions. The phospho-CREB (P-CREB) phosphatase activity present in nuclear extracts coelutes with protein Ser/Thr phosphatase type 2A (PP2A) on Mono Q, amino-hexyl Sepharose, and heparin agarose columns and was chromatographically resolved from nuclear protein Ser/Thr-phosphatase type 1 (PP1). Furthermore, P-CREB phosphatase activity in nuclear extracts was unaffected by the heat-stable protein inhibitor-2, which is a potent and selective inhibitor of PP1. Nuclear PP2A dephosphorylated P-CREB 30-fold more efficiently than did nuclear PP1. Finally, when PKA-phosphorylated CREB was treated with immunopurified PP2A and PP1, the PP2A-treated CREB did not stimulate transcription from the PEPCK promoter in vitro, whereas the PP1-treated CREB retained the ability to stimulate transcription. Nuclear PP2A appears to be the primary phosphatase that dephosphorylates PKA-phosphorylated CREB.